2020
DOI: 10.1111/vec.13031
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of additive solutions on the development of storage lesions in stored canine platelet concentrates

Abstract: Objective To determine if platelet additive solutions (PAS) decrease the occurrence and degree of platelet storage lesions, maintain platelet function, and extend storage time in vitro beyond 5 days at 22°C when compared to platelets stored in plasma only. Design Prospective, ex vivo experimental controlled study. Setting Research laboratory in a school of veterinary medicine. Animals Twelve units of canine platelet concentrate prepared from fresh whole blood donations. Interventions Platelet concentrates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 48 publications
2
27
3
Order By: Relevance
“…34,35 The maximum aggregation seen in this study was also higher than what was seen in a canine study of room temperature-stored PC in PAS. 16 Aggregates suggest platelet activation; however, in this study the presence of aggregates at 1 day did not always result in aggregates present at later days, likely indicating that any activation that occurred was reversible. Previous studies in human medicine have demonstrated that cold storage induced an increase in aggregate formation, but storing the platelets in PAS at 4 • C resolved aggregate formation and preserved the metabolic and functional responses.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…34,35 The maximum aggregation seen in this study was also higher than what was seen in a canine study of room temperature-stored PC in PAS. 16 Aggregates suggest platelet activation; however, in this study the presence of aggregates at 1 day did not always result in aggregates present at later days, likely indicating that any activation that occurred was reversible. Previous studies in human medicine have demonstrated that cold storage induced an increase in aggregate formation, but storing the platelets in PAS at 4 • C resolved aggregate formation and preserved the metabolic and functional responses.…”
Section: Discussioncontrasting
confidence: 63%
“…When the pH drops below 6.2, platelets begin to activate, leading to a further increase in metabolism that perpetuates the cycle, causing decreased platelet recovery after transfusion, shorter survival times, and reduced ability to stop bleeding 13,14 . Evaluation of PC for storage lesions involves in vitro assessment of metabolic changes, changes in platelet shape and function, platelet activation, and evidence of platelet lysis 5,6,15,16 …”
Section: Introductionmentioning
confidence: 99%
“…We suggest that PLT lysis is already evident after one freezing step, which was necessary to store the concentrates until the ELISA analyses were performed, or there could be an effect of the filter or plastic surface of the storage tubes on the growth factors concentrations. This will require further studies and it could also be considered to replace the plasma in the PLT concentrate production completely or partially by additive solutions, on the one hand to preserve plasma for the patients, and on the other hand because it has already been shown that these solutions improve the stability of the product [ 56 ]. Last but not least, an interesting difference between dogs and horses was observed regarding the correlations between donor age and PLT and growth factor concentrations, which were negative in horses [ 29 , 57 ] but positive in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…30 PSLs occur due to platelet metabolism, 15 and decrease platelet viability and hemostatic activity after transfusion and immunity. 15,30,31 Platelets are metabolically active and depend on adenosine triphosphate (ATP) hydrolysis for survival and function. 15 About 85% of ATP is produced by mitochondrial respiration in the tricarboxylic acid cycle (TCA).…”
Section: Discussionmentioning
confidence: 99%
“…PF4, β ‐TG, and P‐selectin are present in the α granules of platelets, and since their expression increases with platelet activation, these proteins have long been recognized as markers of PSLs in transfusion medicine 30 . PSLs occur due to platelet metabolism, 15 and decrease platelet viability and hemostatic activity after transfusion and immunity 15,30,31 . Platelets are metabolically active and depend on adenosine triphosphate (ATP) hydrolysis for survival and function 15 .…”
Section: Discussionmentioning
confidence: 99%